2016
DOI: 10.1039/c6cp03028a
|View full text |Cite
|
Sign up to set email alerts
|

A first-principles study of pressure-induced phase transformation in a rare-earth formate framework

Abstract: Among the panoply of exciting properties that metal-organic frameworks (MOFs) exhibit, fully reversible pressure-induced phase transformations (PIPTs) are particularly interesting as they intrinsically relate to the flexibility of MOFs. Recently, a number of MOFs have been reported to exhibit this feature, which is attributed to bond rearrangement with applied pressure. However, the experimental assessment of whether a given MOF exhibits PIPT or not requires sophisticated instruments as well as detailed struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In order to better understand the structure–property relationship in this family of compounds, it is important to search for frameworks templated by novel protonated amines and study such compounds in a broad temperature range. Recently, pressure is emerging as another important parameter that can help to understand properties of these materials. For instance, it has been shown that pressure may enhance ferroelectric properties or lead to novel phases with potentially useful properties, which are not accessible at ambient conditions …”
Section: Introductionsupporting
confidence: 54%
“…In order to better understand the structure–property relationship in this family of compounds, it is important to search for frameworks templated by novel protonated amines and study such compounds in a broad temperature range. Recently, pressure is emerging as another important parameter that can help to understand properties of these materials. For instance, it has been shown that pressure may enhance ferroelectric properties or lead to novel phases with potentially useful properties, which are not accessible at ambient conditions …”
Section: Introductionsupporting
confidence: 54%
“…5). 94,95 The coordination number of the M 3þ ion is unchanged in the process. A similar mechanism operates in CoCl 2 bpp [bpp ¼ 1,3-bis(4-pyridyl)propane], as Cl À ligands switch to bridging Co centers in the high-pressure phase.…”
Section: Reconstructive Phase Transitionsmentioning
confidence: 99%
“…High-pressure data of MOFs are of great interest since they provide information on pressure dependence of intermolecular interactions, stability of the structure and the properties of highpressure polymorphs that may have significantly different properties from the parent phase. 10,18,35,36 High-pressure data are therefore important for future technological applications and understanding the structure-property relationship for this crystal.…”
Section: Introductionmentioning
confidence: 99%